2018
DOI: 10.1002/adbi.201700257
|View full text |Cite
|
Sign up to set email alerts
|

Towards Cellular Sieving: Exploring the Limits of Scaffold Accessibility for Cell Type Specific Invasion

Abstract: of directing the regeneration of such complex tissues, a detailed understanding of the cell type dependent link between scaffold structure and cell motility is therefore required. In this work, we describe how this cell type dependence may be exploited toward cellular sieving: scaffold structures that permit differing degrees of invasion according to cell type. By comparing the invasion behavior of cells from three different sources, in scaffolds of systematically increasing accessibility, we probe the structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Indeed, it was demonstrated that cell speed at pore wall junctions is lower than the speed along the pore walls regardless of the pore size. As a consequence, high interconnectivity and large pores enhance cell speed, since the time spent at pore wall junctions is decreased [69,73,75,76]. In addition, if cell speed decreases when cells travel on larger pores, cells travel further into the scaffold due to a less erratic and more directional movement.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it was demonstrated that cell speed at pore wall junctions is lower than the speed along the pore walls regardless of the pore size. As a consequence, high interconnectivity and large pores enhance cell speed, since the time spent at pore wall junctions is decreased [69,73,75,76]. In addition, if cell speed decreases when cells travel on larger pores, cells travel further into the scaffold due to a less erratic and more directional movement.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has demonstrated that the structural characteristics of collagen scaffolds may be controlled to a much greater extent than previously acknowledged. In particular, it has been shown that pore size, anisotropy, and the availability of transport pathways are independently variable in collagen scaffolds, each with a distinct, cell-type specific influence on cell invasion [ 12 14 ]. The effects of such parameters on cell motility have been studied rigorously in isolation; for instance, it is known that lower pore sizes tend to inhibit cell dispersion towards the centre of scaffold constructs, whereas anisotropic scaffolds lead to elongated cells and enhanced migration relative to isotropic scaffolds [ 8 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Naturally-derived polymers, such as collagen, gelatin, and chitosan, have the advantages of presenting good biocompatibility with the host cells while being biologically active and promoting cell adhesion and proliferation for the regeneration of damaged tissues. [67] In addition, tissue-engineered scaffolds composed of natural polymers undergo a successful integration with the host tissue for tissue remodelling, thus presenting reduced immune reaction. However, naturally derived polymers present several disadvantages when fabricating tissue-engineered scaffolds.…”
Section: Biodegradable Materialsmentioning
confidence: 99%